MAINTAINING INTEGRITY: FRAUD HEXAGON ANALYSIS ENHANCING FINANCIAL STATEMENT FRAUD DETECTION - Anggraeni, Firda; Suhadi, Suhadi; Hardiningsih, Pancawati (Universitas Jember, 2024)
ABSTRACTThe objective of this study is to examine financial statement fraud through the lens of the fraud hexagon theory, which takes into account factors such as industry nature, CEO duality, external pressure, financial stability, ineffective monitoring, director changes, total accrual ratio, and political connections. Twelve securities that are listed on the Jakarta Islamic Index (JII) for before the pandemic (2018-2019) periods and the pandemic period (2020-2022) periods make up this research sample. This study applies Eviews 12 to panel data regression analysis techniques. According to this study, financial statement fraud is positively impacted by financial stability. Then, false financial statements are negatively impacted by the nature of the industry. External pressure, inadequate oversight, director changes, total accrual ratios, political ties, and CEO duality, on the other hand, do not appear to have any bearing on financial report manipulation. Based on this research, it is hoped that companies will disclose financial reports that reflect the real situation. Future researchers are advised to expand the sample scope and add different indicators to test factors in the hexagon fraud theory.Keywords: Fraud Hexagon; Financial Performance; Financial Report Fraud; Financial Stability; Non-Financial Performance ABSTRAKPenelitian ini bertujuan menganalisis kecurangan laporan keuangan melalui teori fraud hexagon, yang diukur dengan external pressure, financial stability, nature of industry, ineffective monitoring, change in director, total accrual ratio, political connection, dan CEO duality. Sampel penelitian ini terdiri dari 12 sekuritas yang tercatat di Jakarta Islamic Index (JII) periode sebelum pandemi (2018-2019) dan periode pandemi (2020-2022). Riset ini memakai teknik analisis regresi data panel dengan mengaplikasikan Eviews 12. Riset ini memperoleh hasil financial stability berpengaruh positif pada kecurangan laporan keuangan. Kemudian nature of industry memiliki pengaruh negatif terhadap kecurangan laporan keuangan. Sementara external pressure, ineffective monitoring, change in director, total accrual ratio, political connection dan CEO duality tidak menggambarkan adanya dampak atas manipulasi laporan keuangan. Berlandaskan riset ini, diharapkan perusahaan mengungkapkan laporan keuangan yang mencerminkan keadaan sesungguhnya. Peneliti berikutnya dianjurkan memperluas cakupan sampel dan menambah indikator berbeda untuk menguji faktor pada teori kecurangan hexagon.Kata Kunci: Fraud Hexagon; Performa Keuangan; Kecurangan Laporan Keuangan; Kinerja Non Keuangan; Stabilitas Keuangan